The Violation of Blacks’ Rights: the Failure of Black People to Preserve their Rights in Toni Morrison’s Fic - Aboubakar Siriki DIARRASSOUBA (Akofena, 2025)
Abstract: The respect of the rights of a community members results from the relationship between them and their ability to preserve those rights. The history of Blacks in America is generally revisited when considering black people as victims of the white oppression. This article through a new way of reading the African American novelist Toni Morrison’s fictions shows how Blacks cannot only be perceived as victims, but responsible of their trauma experience and the injustice towards them. The analysis of the notions of Individualism, egoism and betrayal that occur within the black community highlights the responsibility of Blacks in the violation of their rights.